Persistent mullerian duct syndrome: A case report and review of the literature - Nayak, Vaibhav J (Medknow Publications & Media Pvt Ltd, 2014)
Persistent mullerian duct syndrome (PMDS) is usually an accidental finding either during orchipexy or during routine inguinal hernia repair in male patients presenting with maldescended or crytorchid testes. It is caused by a defect in the mullerian inhibiting substance system. Intraoperatively, mullerian remnants consisting of an infantile uterus and fallopian tubes are usually found. Familiarity with PMDS is necessary to diagnose the condition. We report a case of PMDS in a 14-year-old male presenting with bilateral undescended testes.